Validation of claims-based diagnostic codes for idiopathic thrombotic thrombocytopenic purpura in a commercially-insured population - Wahl, Peter M; Terrell, Deirdra R; George, James N; Rodgers, J Keith; Uhl, Lynn; Cataland, Spero; Bohn, Rhonda L (Thrombosis and haemostasis, 2010)
It was the purpose of the present study to validate administrative claims codes for idiopathic thrombotic thrombocytopenic purpura (TTP) in a commercially-insured US population. Patients with at least one medical claim with ICD-9 code 446.6X between 1/1/2001 and 5/31/2008 were identified in the HealthCore Integrated Research Database (HIRD). A chart abstraction form was developed to enable case determination for patients identified by the claims code. Two clinical experts, not involved in the design of the study, reviewed the abstracted medical record data and determined whether definite evidence supporting the diagnosis of TTP was present. The positive predictive value (PPV) of the claims coding algorithm for cases assessed by both reviewers was computed. The claims algorithm was further refined and the PPV of the refined algorithm was computed. One hundred eighty-nine abstracted charts were reviewed by two clinical experts; 86 were assessed to have definite evidence supporting the diagnosis of TTP (PPV 45.5% [86/189; 95% confidence interval (CI), 38.3-52.9%]). Refinement of the claims algorithm first included the use of plasma exchange treatment, resulting in 103 potential cases, of which 67 were assessed to have definite evidence supporting the diagnosis of TTP (PPV 65.0%; 95% CI, 55.0-74.2%). Further refinement of the claims algorithm ruled out alternative diagnoses that may mimic TTP; 34 were assessed to have definite evidence supporting the diagnosis of TTP (PPV 72.3% [34/47; 95% CI, 57.4-84.4%]).Our findings demonstrate the difficulty of confirming the diagnosis of rare disorders that lack definite diagnostic criteria, and indicate that more complex claims coding algorithms are necessary for identifying these disorders.